Effects of surfactants on the molecular aggregation of squaraine dye Sq-2Me in aqueous solutions - Yefimova, S.L.; Guralchuk, G.Ya.; Lebed', A.S.; Sorokin, A.V.; Malyukin, Yu.V.; Kurilchenko, I.Yu. (Functional Materials, 2009)
The influence of anionic surfactant, sodium dodecyl sulphate (SDS), and cationic one, cetylpyridinium bromide (CPB), on aggregation behavior of squaraine dye Sq-2Me has been studied in aqueous solutions by optical spectroscopy. It has been found that the addition of surfactants at concentrations higher than critical micelle one CIIJ,TcyTeK<lJemr:u.T into a DMF-W (95 %) solution does not prevent the dye aggregation. The structure of Sq-2Me aggregates formed in SDS and CPB micelles is discussed using the exciton theory. The results show that the optical properties and the Sq-2Me aggregate structure can be tuned using interaction with surfactant micelles of different nature. У водних розчинах методами оптичної спектроскопії вивчено вплив аніонної (додецилсульфат натрію, SDS) та катіонної (цетилпіридиній бромід, СРВ) поверхнево-активних речовин (ПАР) на агрегацію сквараїнового барвника Sq-2Me. Встановлено, що додавання у бінарний розчин ДМФ-В (95 %) ПАР у концентрації, вищій за критичну концентрацію міцелоутворення, не перешкоджає агрегації барвника. Структуру агрегатів барвника Sq-2Me, що утворюються у міцелах ПАР, розглянуто у рамках екситонної теорії. Отримані результати дозволяють зробити висновок, що структурою агрегатів Sq-2Me можна керувати за допомогою ПАР різної хімічної будови. В водных растворах методами оптической спектроскопии изучено влияние анионного (додецилсульфат натрия, SDS) и катионного (цетилпиридиний бромид, СРВ) поверхностно- активных веществ (ПАВ) на агрегацию сквараинового красителя Sq-2Me. Обнаружено, что добавление в бинарный раствор ДМФ-В (95 %) ПАВ в концентрации выше критической концентрации мицеллообразования не препятствует агрегации красителя. Структура агрегатов красителя Sq-2Me, образованных в мицеллах SDS и СРВ, рассматривается в рамках экситонной теории. Полученные результаты позволяют сделать вывод о возможности управления структурой агрегатов Sq-2Me при помощи ПАВ разной химической природы.